Analysis of Investment Feasibility for the Wonderlife Hotel Development Project in Pangandaran Based on Financial Aspect - Dede Hilman; Kharisya Ayu Effendi (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The increasing tourism activities in Pangandaran Tourist Destination must be supported by adequate facilities and infrastructure, particularly accommodation. Pondok Seni Pangandaran, owned by the Department of Culture and Tourism of West Java Province, needs to be revitalized to compete with other hotels. Through the Build Operate Transfer (BOT) cooperation scheme, private sector involvement is expected in investing in the revitalization of Pondok Seni Pangandaran. However, a feasibility study is required to determine the financial viability of the investment, including calculations of NPV, Profitability Index, Payback Period, and IRR. From the feasibility analysis, the investment shows a cash inflow of Rp. 555,712,698,655.00; projected profit and loss of Rp. 45,026,582,596.00 over a 30-year operating period; NPV of IDR 17,962,228,160.00; Profitability Index of 2.53; Payback Period of 10 years from the construction period and 8 years from the operational period; and IRR of 13.17%. In conclusion, the investment in the Wonderlife Hotel development project in Pangandaran is deemed feasible.